2021
DOI: 10.1111/corg.12400
|View full text |Cite
|
Sign up to set email alerts
|

Founder teams and firm value in young public firms: An analysis of the moderating effect of founders' ownership power and team size

Abstract: Research Question/Issue Building on prior work on the relationship between founder ownership and firm value in young public firms, we test the moderating influence of the presence of cofounders, distinguishing between dyads and teams of three or more founders. Research Findings/Insights We test our hypotheses on a unique sample of 7162 observations from 959 US firms that have been public for less than 20 years and retained their founders. We show that the presence of one or more cofounders has distinct moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…Interactions among executives in new ventures are more frequent than those in established firms (Talaulicar, 2020). Thus, scholars posit that focusing on established firms provides narrow insights and limits the generalizability of corporate governance literature (Dawson et al, 2021). Especially nowadays, they emphasize that it is imperative for us to shift insights from large established firms to new ventures (Dawson et al, 2021; Talaulicar, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions among executives in new ventures are more frequent than those in established firms (Talaulicar, 2020). Thus, scholars posit that focusing on established firms provides narrow insights and limits the generalizability of corporate governance literature (Dawson et al, 2021). Especially nowadays, they emphasize that it is imperative for us to shift insights from large established firms to new ventures (Dawson et al, 2021; Talaulicar, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, scholars posit that focusing on established firms provides narrow insights and limits the generalizability of corporate governance literature (Dawson et al, 2021). Especially nowadays, they emphasize that it is imperative for us to shift insights from large established firms to new ventures (Dawson et al, 2021; Talaulicar, 2020). By focusing on the CEO–CFO dyad in the context of new ventures, we can have an improved understanding of the role that the subteam of TMT plays in influencing new venture fraud.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiu et al [14] also concluded that CEO power has a direct positive effect on the firm's financial performance. Finally, [15] also found that the characteristics of the board of directors and the CEO significantly contribute to a firm's market value. H1 = CEO Power has a positive and significant effect on Firm Value.…”
Section: Introductionmentioning
confidence: 91%
“…Beyond a potential theoretical explanation, whether the relationship is positive or negative typically depends on certain moderators (team size and gender diversity) (Dawson et al, 2022; Poletti‐Hughes and Martinez Garcia, 2022; Kabore et al, 2021; Lauring & Villesèche, 2019; Li, 2018; Ruiz‐Jiménez et al, 2016; Backes‐Gellner et al, 2015a; Vaccaro et al, 2012). Based on social identity theory, team size is viewed as a critical boundary condition for affecting team partnership (Sui et al, 2016; Levine & Crowther, 2008) and a pivotal characteristic shaping internal team dynamics (Stewart, 2006).…”
Section: Introductionmentioning
confidence: 99%